Optimizing Safety, Predictability, and Aesthetics in Direct to Implant Immediate Breast Reconstruction: Evolution of Surgical Technique. (June 2016) - Kalus, Ram; Dixon Swartz, Jennifer; Metzger, Sarah Cristina
Abstract : Background: Although immediate breast reconstruction with the insertion of a permanent prosthesis rather than a tissue expander (direct to implant [DTI]) has become gradually more preferred and requested by patients, the technique has yet to be fully embraced by most plastic surgeons, presumably due to concerns of patient safety and perceived higher complication and revision rates, despite not being supported by the literature. Objectives: The authors review the senior author's protocol for patient selection and surgical technique in DTI reconstructions. A simple device is introduced which adds predictability and control in determining the inset suture line for the acellular dermal matrix and thus the position of the inframammary fold and lateral mammary fold, resulting in improved aesthetic outcomes, reduced complications, and reduced reoperation rates. Methods: A retrospective review of our one surgeon experience with 134 DTI breast reconstructions in 77 patients between 2006 and 2015 is presented. The series is further subdivided into 74 reconstructions in 43 patients in whom their reconstruction was performed before the use of a patented 2-dimensional (2-D) template, and 60 reconstructions in 34 patients in whom the template was used. Results: The overall complication rate requiring reoperation in the first 54 reconstructions was 50% versus 15% in the last 84. Failure of the reconstruction, defined by explantation, occurred in 11 of 74 reconstructions (14.9%) before the use of 2-D templates, and in 5 of 60 reconstructions (8.3%) in which templates were used, representing a 44% reduction. The revision rate specifically for implant malposition dropped from 18.6% before the use of templates to 2.9% after the incorporation of templates. Fifty-three reconstructions in 33 patients (40%) had no complications and no reoperations, correctly described as "one and done." Conclusions: Direct to implant reconstruction can be technically more demanding and exacting than 2-stage expander/implant reconstructions. A review of this single surgeon series confirms that despite a learning curve with a higher complication rate early in the series, in the setting of proper patient selection DTI immediate reconstruction is both safe and reliable, and can potentially have clinical, psychological, and aesthetic advantages for patients when compared with a 2-stage expander/implant reconstruction, with 40% of patients having 1 operation only. The use of a patented 2-D template has reduced complications and the rate of reoperation.